ELSA-Brasil strategies for outcome identification, investigation and ascertainment - Barreto, Sandhi Maria; Ladeira, Roberto Marini; Bastos, Maria do Socorro Castelo Branco de Oliveira; Diniz, Maria de Fatima Haueisen Sander; Jesus, Elcimara Amorim de; Kelles, Silvana Marcia Bruschi; Luft, Vivian Cristine; Melo, Enirtes Caetano Prates; Oliveira, Elizabete Regina Araujo de (Revista de Saúde Pública, 2013)
OBJECTIVE: The article describes the strategies adopted by the Brazilian Longitudinal Study for Adult Health (ELSA-Brasil) for participation and retention of subjects. This is key to ensure internal validity of longitudinal studies, and to identify, investigate, and ascertain outcomes of interest. METHODS: The follow-up strategies include annual telephone contacts with new assessments and interviews every three to four years this approach aims to identify transient outcomes (reversible or not), permanent outcomes as well as complications related to the progression of major diseases - cardiovascular diseases and diabetes - to be studied. RESULTS: Telephone interviews are designed to monitor subjects' health status and to identify potential health-related events such as hospital admissions, medical visits or pre-selected medical procedures. Subjects are also encouraged to report to the ELSA-Brasil team any new health-related events. When a potential event is identified, a thorough investigation is carried out to collect relevant information about that event from medical records. All data are blinded and reviewed and analyzed by a medical expert committee. Incident outcome ascertainment follows well-established international criteria to ensure data comparability and avoid misclassification. In addition to these strategies, the occurrence of health-related events is also investigated through linkage of secondary databases, such as national mortality and hospital admission databases. CONCLUSIONS: Accurate identification of outcomes will allow to estimating their incidence in the study cohort and to investigate the effect of the exposures studied in the ELSA-Brasil at baseline and at its subsequent waves.